Ocean Acidification Changes Abiotic Processes but Not Biotic Processes in Coral Reef Sediments - Fink, Artur; den Haan, Joost; Chennu, Arjun; Uthicke, Sven; de Beer, Dirk (Frontiers in Marine Science, 2017)
In coral reefs, sediments play a crucial role in element cycling by contributing to primary production and the remineralization of organic matter. We studied how future ocean acidification (OA) will affect biotic and abiotic processes in sediments from two coral reefs of the Great Barrier Reef, Australia. This was investigated in the laboratory under conditions where water-sediment exchange was dominated by molecular diffusion (Magnetic Island) or by porewater advection (Davies Reef). OA conditions (+ΔpCO2: 170–900 µatm, -ΔpH: 0.1–0.4) did not affect photosynthesis, aerobic and anaerobic organic matter remineralization and growth of microphytobenthos. However, microsensor measurements showed that OA conditions reduced the porewater pH. Under diffusive conditions these changes were limited to the upper sediment layers. In contrast, advective conditions caused a deeper penetration of low pH water into the sediment resulting in an earlier pH buffering by dissolution of calcium carbonate (CaCO3). This increased the dissolution of Davis Reef sediments turning them from net precipitating (-0.8 g CaCO3 m-2 d-1) under ambient to net dissolving (1 g CaCO3 m-2 d-1) under OA conditions. Comparisons with in-situ studies on other reef sediments show that our dissolution rates are reasonable estimates for field settings. We estimate that enhanced dissolution due to OA will only have a minor effect on net ecosystem calcification of the Davies Reef flat (< 4%). However, it could decrease recent sediment accumulation rates in the lagoon by up to 31% (by 0.2–0.4 mm year-1), reducing valuable reef space. Furthermore, our results indicate that high-magnesium calcite is predominantly dissolving in the studied sediments and a drastic reduction in this mineral can be expected on Davis Reef lagoon in the near future, leaving sediments of an altered mineral composition. This study demonstrates that biotic sediment processes will likely not directly be affected by OA. Ensuing indirect effects of OA-induced sediment dissolution on biotic processes are discussed.